The impact challenge: Reframing sustainability for businesses - Alessia Falsarone (CRC Press, 2022)
This book explores the role of businesses in delivering positive societal and financial outcomes as they seek to bridge the gap between short-term organizational behaviors and long-range sustainability commitments. By addressing the inevitable data challenges associated with the strategic integration of a sustainability mindset, it enables faster adoption of social, environmental and governance metrics that generate lasting enterprise value. Inspired by the experience of practitioners that have successfully influenced the learning behaviors of complex organizations, this book helps readers drive systemic innovations as they leverage sustainability initiatives in a programmatic and intentional manner. Features: Defines a toolkit to generate sustainable business value by focusing on the organizational design underpinning sustainability-oriented initiatives. Provides a multidisciplinary lens on shaping the impact dialogue through applied frameworks. Discusses the need to analytically identify an organizational learning curve before developing impact targets and framing sustainability commitments around them. Combines theory and practice in a practical style by presenting a variety of real-life applications at a global level.
Keywords: 330; Business Innovation; Data Science; Environment; Finance; Sustainability; Sustainable development goals